ANALISA DAN KLASIFIKASI SENTIMENT OPINI PENONTON PADA WEBSITE IMDB.COM DENGAN ALGORITMA SUPPORT VECTOR MACHINE - Akhmad Budi, S.Kom., MM., M.Kom (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
In its development, information technology brought about many changes and advances in the context of everyday life. One of the benefits of information technology to process and process large amounts of data is data mining and text mining. In this study the authors will analyze and discuss the sentiment (emotion) contained in a comment or post on reviews given by the audience on a movie and see whether it will be classified as positive sentiment or negative so that it can be used to classify the reviews on different movies at imdb.com in the future. This research will gain some classification models based on modeling with support vector machine algorithm to classify the opinion of the new movie and the level of accuracy of each models. Also there will be a wordlist data that contains details of each positive and negative comments in the classification process. Results of this study indicate that it is possible to create a classification model based on audience opinions to classify new opinion using support vector machine algorithms with a high degree of accuracy and produce the details of words in the wordlist database to find a word or phrase that affects most to determine the sentiment in an opinion.Keywords : Classification, Opinion, Audience, Movie, Website, Data Mining, Text Mining, Sentiment Analysis, Support Vector Machine